2008
DOI: 10.1369/jhc.2008.950956
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytological and Preliminary Immunohistochemical Studies of Prothymosin α, a Human Cancer–associated Polypeptide, With a Well-characterized Polyclonal Antibody

Abstract: Prothymosin α (ProTα) is a nuclear polypeptide of great biological and, possibly clinical, importance, because its expression levels have been associated with early diagnosis/prognosis of human cancer. It is therefore interesting to raise easily available and cost-effective antibodies that would be applied to develop reliable ProTα immunodiagnostics. In this study, New Zealand white rabbits and laying hens were parallel immunized against intact ProTα or the synthetic fragments ProTα[1-28], ProTα[87-109], and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
12
1
1
Order By: Relevance
“…The above results were confirmed by suitably treating HeLa cells, so as to remove their cytoplasm, and then staining the cell nuclei. Contrary to that obtained with the anti-BAL antiserum and with streptavidin, clear nuclear staining (data not shown here) was observed with the positive control, i.e., a wellcharacterized rabbit antiserum recognizing the nuclear polypeptide prothymosin alpha [17].…”
Section: Evaluation Of the Anti-bal Antibodies In Immunocytology Expecontrasting
confidence: 90%
See 1 more Smart Citation
“…The above results were confirmed by suitably treating HeLa cells, so as to remove their cytoplasm, and then staining the cell nuclei. Contrary to that obtained with the anti-BAL antiserum and with streptavidin, clear nuclear staining (data not shown here) was observed with the positive control, i.e., a wellcharacterized rabbit antiserum recognizing the nuclear polypeptide prothymosin alpha [17].…”
Section: Evaluation Of the Anti-bal Antibodies In Immunocytology Expecontrasting
confidence: 90%
“…A rabbit polyclonal antibody that recognizes the nuclear polypeptide prothymosin alpha [17] was used as a positive control for nuclear staining.…”
Section: Evaluation Of the Anti-bal Antibodies In Immunocytology Expementioning
confidence: 99%
“…By immunohistochemistry and immunoblotting, they showed that proT levels consecutively increased as prostate tissue progressed from normal epithelium, through prostatic intraepithelial neoplasia to carcinoma [56]. Particularly, in prostate cancer lesions, intense nuclear staining for proT was also reported [57]. Subsequent complementary research investigated proT expression in human bladder cancer using tissue microarrays [58].…”
Section: The Dual-intracellular and Extracellular-role Of Protmentioning
confidence: 99%
“…Subsequent complementary research investigated proT expression in human bladder cancer using tissue microarrays [58]. A statistically signiWcant enhancement of proT expression, also from the clinical aspect, was Colon mRNA in tissue c-myc expression [45,52] Gastric Protein in tissue - [63] Head and neck Protein in tissue Tumor recurrence [62] Liver mRNA in tissue; protein in tissue c-myc expression; poor prognosis [46,60] Lung mRNA in tissue Poor prognosis [48] Neuroblastoma mRNA in tissue N-myc expression [47] Pituitary Protein in tissue Tumor recurrence [61] Prostate Protein in tissue Cancer cell diVerentiation; tumor progression [56,57] Rectal mRNA in tissue EVectiveness of radiotherapy [51] Rhabdomyosarcoma mRNA in tissue - [49] Thyroid mRNA in tissue; protein in tissue and serum…”
Section: The Dual-intracellular and Extracellular-role Of Protmentioning
confidence: 99%
“…the antibody for tg-2 was purchased from santa cruz Biotechnology (santa cruz, CA, USA) for fluorescence immunocytochemistry analysis. Fluorescence immunocytochemistry was done using a previously published method (14). 4',6-Diamidino-2-phenylindole (DAPI) was used for count staining.…”
Section: Fluorescence ιMmunocytochemistry and Real-time Polymerase Chmentioning
confidence: 99%